A Case for Cross-Cultural Religious Literacy - Seiple, Chris (The review of faith & international affairs, 2021)
Cross-cultural religious literacy is a comprehensive approach to understanding and conducting the kind of engagement that distinguishes robust, covenantal pluralism from merely indifferent “tolerance” of diversity. Such an approach teaches, respectively, the personal and comparative competencies of knowledge about self, and about the other, as well as the collaborative context in which this knowledge is applied. This approach also teaches the skills—evaluation, negotiation, and communication—of moving toward the other such that shared goals can be identified and implemented.